Experimental study on crushing of concrete columns by high voltage pulse discharge. (June 2022) - Wang, Xiaodong; Du, Jiaxu; Li, Qiang
Abstract: High voltage pulse discharge (HVPD) crushing tests were carried out on 30 concrete columns with section sizes of 400 mm × 400 mm, 500 mm × 500 mm, 600 mm × 600 mm and 700 mm × 700 mm respectively. Based on the comparative analysis of the electrohydraulic effect and the copper wire explosion on the fracture test of a concrete beam, the latter is determined as the optimal method. The parameters in the test of crushing concrete columns by HVPD include strength grade of concrete, column borehole aperture, hole spacing, discharge voltage and number of copper wires. Columns with sectional dimensions of 400 mm × 400 mm and 500 mm × 500 mm are arranged in single row boreholes, and columns with sectional dimensions of 600 mm × 600 mm and 700 mm × 700 mm are arranged in double rows of boreholes. The results show that the crushing effect of concrete columns increases obviously with the increase of discharging voltage and the number of copper wires, and slightly increases with the decrease of concrete strength. When other parameters are the same, the crushing effect of the concrete columns with hole diameter of 40 mm is better than that of the ones with hole diameter of 50 mm. The crack connectivity of concrete columns with hole spacing of 300 mm is similar to that of the ones with hole spacing of 400 mm. According to the test results, the mathematical expressions of the damage degree of concrete columns with single and double rows of holes (i.e., the width of concrete cracks around boreholes) and the output voltage, the number of copper wires and the strength grade of concrete are established respectively. In order to meet the needs of the project, the suggestion of further crushing construction combined with mechanical method was put forward